Biopolitical Strategies in Media Discourses: Responses to the COVID-19 Pandemic in Russia, Germany, and France - N. K. Radina; Yu. V. Balakina; K. V. Bannikov (Vestnik MGIMO-Universiteta, 2024)
The objective of this study is to conduct a comparative analysis of how media outlets in Russia, France, and Germany reported on events during the COVID-19 pandemic. The analysis was carried out in three stages: comparing the actors of biopolitics, examining the ideologemes of biopolitics, and analyzing the spheres in which biopolitics were implemented. The theoretical and methodological framework of this study is grounded in Michel Foucault's theory of biopolitics, Edward Herman and Noam Chomsky's propaganda model, and Didier Bigo's concept of (in)securitization. Texts related to the COVID-19 pandemic were categorized into four «waves» (January 2020 – March 2022) and retrieved using the keywords «pandemic», «covid», and «coronavirus» from the archives of «Rossiyskaya Gazeta», «Kommersant», «Novaya Gazeta», «Le Figaro», «Le Monde», «Le Parisien», «Süddeutsche Zeitung», «Die Zeit», and «Die Tageszeitung». The total volume of analyzed material amounts to 67.62 million words. The results reveal that state power consistently emerges as a key subject of biopower and biopolitics across all the media studied, following Foucault's traditional framework of biopower subjects. This includes a focus on the actions and decisions of government officials and institutions. Additionally, the study found that all examined media outlets participated in promoting vaccination campaigns orchestrated by the governments of Russia, Germany, and France, indicating a widespread alignment with state-led biopolitical strategies.The analysis also shows that the insecuritization of public life during the pandemic affected various sectors including social relations, the economy, healthcare, and education. Media discourse in all three countries highlighted these areas of impact, often framing them within the broader context of public and existential security.Furthermore, the study identifies notable differences in how the media in each country portrayed biopolitical themes. In Russia, media coverage placed a strong emphasis on the central government's role, while in Germany, there was a more pronounced delineation between federal and regional authorities. In France, media outlets often focused on the personal leadership of President Emmanuel Macron. Despite these differences, there were shared themes across all three countries, such as the emphasis on the importance of vaccination and the portrayal of government measures as necessary for public safety.